2021
DOI: 10.1139/apnm-2020-0277
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weather conditions on children’s school travel mode and physical activity in 3 diverse regions of Canada

Abstract: Children who engage in active school transportation (AST) have higher levels of physical activity (PA). Climate and weather were shown to influence adults' daily travel behaviours, but their influence on children's AST and PA has been less examined. This study examined the influence of weather conditions on children’s active school transportation (AST) and overall physical activity (PA). Children in grades 4 to 6 (N=1,699; 10.2 ± 1.0 years old) were recruited in schools located in urban, suburban and rural are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…Consistent with previous studies, cold and wet conditions were seen as a barrier to AST [ 1 , 25 , 30 ]. Many adolescents indicated that the cold and wet weather makes it hard to walk, cycle, or ride a non-motorised vehicle to school.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, cold and wet conditions were seen as a barrier to AST [ 1 , 25 , 30 ]. Many adolescents indicated that the cold and wet weather makes it hard to walk, cycle, or ride a non-motorised vehicle to school.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies that used games and gamification on children to promote AST received positive feedback from parents, peers, and school officials and noted that gamification helped children feel motivated and engaged using AST [ 10 , 34 ]. There are various motivations behind people's participation in gamification-based interventions such as competition, gaining rewards, socialising, and exploring their local area [ 30 ]. Despite the number of game design techniques used in practice, the concept of gamification needs to be better established, and there is a need for more theoretical frameworks in developing these interventions in the context of AST [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bad weather conditions affected cycling rates for both boys and girls at both school levels. This finding aligns with some research on active travel to school in Canada [32] but contradicted other findings albeit from the Netherlands [33] where active travel rates to school are significantly higher. Cycling rates may be more affected by bad weather conditions than walking and as this analysis considers cycling behaviours only, it is unsurprising that bad weather had a significant negative affect on cycling.…”
Section: Discussionsupporting
confidence: 85%
“…Concerns about weather were identified by participants; however, this was not extensively discussed. Several studies in the literature have reported bad weather as a barrier to physical activities [64,65], including cycling [66]. However, Tremblay et al [67] noted that weather might not be a major barrier to active transport in adolescents.…”
Section: Weathermentioning
confidence: 99%
“…Participant 4 described these concerns by highlighting the concerns about books, [and] laptops getting wet. Therefore, strategies to help adolescents adapt to bad weather are necessary to mitigate this barrier [64].…”
Section: Weathermentioning
confidence: 99%